RESEARCH OF TIME MANAGEMENT METHODS AND THEIR USE IN THE ACTIVITIES OF CIVIL SERVANTS - Lashenko, Oksana; Serohin, Serhii; Serogina, Natalia (Pressing Problems of Public Administration, 2021)
Our country pursues a strategic direction of joining the European community, this fact creates more and more requirements on the government and civil servants. High-quality and timely fulfillment of the undertaken obligations, effective performance of the official duties assume ability to organize effectively both working and personal time, to plan and coordinate actions for performance of the tasks. The lack of time problem is the main one faced by the mass of employees, and the correct use of time is the key to successful performance of professional duties, achievement of goals in any field of activity including public administration. Every civil servant, as a subject of management, strives to perform his professional duties well, but the organization of the management process is conditioned by the emergence of a large number of situations that need immediate resolution (within its competence): consideration of applications, complaints, urgent meetings, etc. In many cases, inefficient use of working time is due to insufficient ability of civil servants to set priorities, plan their activities, manage time and human resources. One of the tools that has been successfully tested in the commercial sphere is time management. Time management combines a set of techniques, methods and technologies that allow the distribution of working and personal time in order to increase the effectiveness of use. Using time management techniques (namely time management tools) civil servants will be able to plan their working day in the most rational way, set priorities in everyday affairs, and focus on the most important aspects of work. The article is dedicated to the essence of time management and the need to use for to improve the effectiveness of working hours in the activities of civil servants. Features of working time planning are revealed. The existing time management methods with the purpose of use during formation of own management working hours system of civil servants are considered. The advantages of using time management in the activities of civil servants are presented. The subject of further scientific research should be the study of methods and technologies of self-control and self-motivation, as well as adaptation of these methods to the activities of civil servants, which will increase the effectiveness of their activities.